1997
DOI: 10.1007/bf02551417
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with neodymium: YAG laser in patients with chronic prostatitis: A preliminary reprot

Abstract: A group of 30 patients with chronic abacterial prostatitis or prostatodynia, all of whom were unresponsive to conventional treatments, underwent transurethral neodymium: YAG laser therapy. The patients were evaluated with both objective and subjective parameters before and after treatment. Following treatment, the preliminary results at six months showed positive response (complete plus partial) rates in subjective parameters ranging from 47% to 86%. On the other hand, objective parameters including mean inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…Thermotherapy [9,10], laser therapy [11,12], or TUNA [13] are currently used for patients with chronic nonbacterial prostatitis unresponsive to traditional therapies. The 10 patients initially treated with transurethral microwave thermotherapy had a significant improvement in quality of life and symptom severity index, but four complained of transient adverse reactions, which included impotence, premature ejaculation and UTI [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermotherapy [9,10], laser therapy [11,12], or TUNA [13] are currently used for patients with chronic nonbacterial prostatitis unresponsive to traditional therapies. The 10 patients initially treated with transurethral microwave thermotherapy had a significant improvement in quality of life and symptom severity index, but four complained of transient adverse reactions, which included impotence, premature ejaculation and UTI [9].…”
Section: Discussionmentioning
confidence: 99%
“…Mene et al [10] suggested that transurethral microwave hyperthermia is a safe and effective treatment for chronic nonbacterial prostatitis. Serel et al [11] reported that in 30 patients with chronic nonbacterial prostatitis who had undergone transurethral Nd:YAG laser therapy, the IPSS, mean quality‐of‐life score, mean uroflowmetry measurements and leukocyte count in EPS showed marked improvements which were significant statistically. Suzuki et al [12] reported that transurethral balloon laser hyperthermia was considered safe and a suitable treatment for patients with chronic prostatitis.…”
Section: Discussionmentioning
confidence: 99%
“…The combined laser treatment proved to be more effective than control, and long-term remission (2 years and longer) was observed in 60% of the patients [47]. Nd-YAG laser also has been used in category IIIA and IIIB prostatitis patients, with a subjective response rate of 47% to 86% [48]. Laser acupuncture [49] and transrectal infrared optic laser therapy [50] also have been used.…”
Section: Lasermentioning
confidence: 99%
“…Exposure to lowintensity laser radiation may diminish symptoms and improve prostatic function by acting as an antiaggregator, contributing to less ejaculate viscosity, and by potential anti-inflammatory and analgesic effect [46]. Nd-YAG laser also has been used in category IIIA and IIIB prostatitis patients, with a subjective response rate of 47% to 86% [48]. Patients in the control group received conventional physiotherapy.…”
Section: Lasermentioning
confidence: 99%